Bioinspired Hierarchical Hydrogel Electrolyte for Ultralong-Life Flexible Zinc-Ion Batteries - Wang, Ran; Gao, Qian; Wu, Runhai; Mi, Yongqi; Yang, Shaopei; Wang, Hongxiao; Wan, Ting; Gull, Sehrish; Xie, Kefeng; Long, Guankui; Du, Pengcheng (Nano-Micro Letters, 2026)
Hydrogel electrolytes are pivotal for flexible zinc-ion batteries (ZIBs) yet suffer from an intrinsic trade-off between mechanical robustness and ionic conductivity. Herein, drawing inspiration from the “adhesion-conduction” architecture of spider webs, we developed a hierarchical hydrogel electrolyte (MTP) by incorporating tannic acid (TA)-modified MXene nanosheets (MT) into a polyacrylamide (PAM) skeleton to construct uniform 3D ion-conductive pathways. This bioinspired hierarchy serves a dual function: The PAM framework ensures mechanical integrity, while the MT network creates directed low-resistance channels for Zn2+ transport. Specifically, the dense array of polar groups on MXene and phenolic hydroxyls on TA act as “sticky sites”, which accelerate desolvation kinetics and homogenize Zn2+ flux. Consequently, the MTP electrolyte achieves an impressive ionic conductivity of 27.69 mS cm−1 and a high Zn2+ transference number of 0.833. Enabled by this design, Zn//Zn symmetric cells demonstrate an ultralong lifespan of 4600 h (> 6 months) at 0.5 mA cm−2/0.5 mAh cm−2. Furthermore, Zn//Z-VO full cells exhibit outstanding cyclability, retaining 74.5% capacity after 2000 cycles at 2 A g−1 and maintaining durable operation for over 10,000 cycles at 5 A g−1. This work successfully translates a biological blueprint into a practical strategy for resolving the kinetic and stability challenges in high-performance flexible ZIBs. Highlights: 1 Drawing inspiration from the “adhesion-conduction” architecture of spider webs, a hierarchical hydrogel electrolyte (MTP) is developed with uniform 3D ion-conductive pathways. 2 Specific “sticky sites” on the MXene/tannic acid network facilitate superior electrochemical properties, including a high Zn2+ transference number of 0.833 and ionic conductivity of 27.69 mS cm−1. 3 This strategy enables stable Zn anodes with an impressive lifespan of 4600 h (>6 months) and empowers flexible full cells with outstanding cyclability over 10,000 cycles.